The Reframing Identity: The Shift of Women’s Images from Traditional Documentaries to Streaming Platforms - Vinlie Antonetta; Muhammad Fakhran Al Ramadhan (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
This paper examines the impact of media representation on public perception and legal outcomes in the high-profile criminal case of Jessica Wongso, who was accused of murdering her friend, Wayan Mirna Salihin. It explores how gendered stereotypes and societal expectations shaped both the media's portrayal of Wongso and the public's perception of her guilt. Traditional media coverage sensationalized her femininity and emotional responses, reinforcing negative stereotypes about women in criminal cases. However, the 2023 documentary Ice Cold: Murder, Coffee, and Jessica Wongso offered a more nuanced perspective, challenging these portrayals and questioning the fairness of the legal proceedings. Through a feminist lens and Émile Durkheim's Mass Society Theory, the paper highlights the intersection of gender, media influence, and legal systems, urging for a more critical and equitable approach to both media coverage and legal treatment of women accused of crimes. It calls for a reassessment of how gender and media shape justice.